2017
DOI: 10.1080/14767058.2017.1378334
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of human placental perfusion by intravoxel incoherent motion MR imaging

Abstract: The observed association between f and fetal weight suggests that fMRI could be suitable for studying placental insufficiency and for identifying risk of SGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 30 publications
8
48
0
Order By: Relevance
“…This value is congruent with the report of Moore et al, who found a mean f of 26% and is also close to the placental f of 32% in healthy pregnancies reported by Sohlberg et al Our findings also match closely the f of the central placenta (35.1%) reported in a previous study and is lower than the mean value (42.5%) reported by Siauve et al, although our observed perfusion fraction is significantly lower than the perfusion values of the decidua basalis reported in normal and small for gestational age subjects . The perfusion fraction as previously found to be a sensitive marker of decreased placental perfusion in murine models and in human studies, and our study confirms the generally accepted range of normal placental perfusion fraction in the central parts of the placenta by means of IVIM. In our study, the placental perfusion fraction was negatively correlated with the umbilical artery resistance index, underscoring the possible importance of IVIM parameters in the evaluation of feto‐placental circulation, but at the same time calls for a careful analysis of such correlations in larger patient samples.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This value is congruent with the report of Moore et al, who found a mean f of 26% and is also close to the placental f of 32% in healthy pregnancies reported by Sohlberg et al Our findings also match closely the f of the central placenta (35.1%) reported in a previous study and is lower than the mean value (42.5%) reported by Siauve et al, although our observed perfusion fraction is significantly lower than the perfusion values of the decidua basalis reported in normal and small for gestational age subjects . The perfusion fraction as previously found to be a sensitive marker of decreased placental perfusion in murine models and in human studies, and our study confirms the generally accepted range of normal placental perfusion fraction in the central parts of the placenta by means of IVIM. In our study, the placental perfusion fraction was negatively correlated with the umbilical artery resistance index, underscoring the possible importance of IVIM parameters in the evaluation of feto‐placental circulation, but at the same time calls for a careful analysis of such correlations in larger patient samples.…”
Section: Discussionsupporting
confidence: 93%
“…There exists, however, an ambiguity in the literature whether the perfusion fraction remains stable (ie, uncorrelated with gestational age) during gestation, or whether it increases or decreases. A recent work by Siauve et al observed an initial increase until the 22 weeks of gestation, a plateau period between 22 and 28 weeks, and a slight decrease in both the apparent diffusion coefficient (ADC) and f values of the placenta . The results of Derwig et al are in line with these findings, as they investigated a relatively narrow gestational age range of 24 to 29 weeks, when, according to Siauve et al, f remains stable .…”
Section: Discussionmentioning
confidence: 60%
“…Intravoxel incoherent motion (IVIM) has been developed and utilized in neuroscience research because of its capability of extracting perfusion information from a diffusion sequence . In a previous study among 55 pregnant women, the f value was suggested to be a suitable tool to reveal placental insufficiency and to identify risk of intrauterine growth retardation . On the other hand, the reproducibility of IVIM MRI to examine microvascular perfusion and diffusion in the developing fetus depends greatly upon data quality, fetal and maternal movements, and fetal‐specific image postprocessing .…”
mentioning
confidence: 99%
“…Results from the BSP fitting approach suggest that the influence of gestational age on MRI parameters should be taken into account. Our results showed linear correlations between the DECIDE estimated parameters and gestational age, although for a wider range of gestational age, non‐linear models may be more appropriate . A wider range of gestational age would help demonstrate the longitudinal trend between the MR parameters during pregnancy which might aid in the prediction of obstetric outcomes.…”
Section: Discussionmentioning
confidence: 75%
“…Assessing normal placental perfusion with gestational age is key to better understand differences linked to placental insufficiency. A recent study has shown changes in IVIM placental parameters, including perfusion and diffusion with gestational age . However, the variability in the measured parameters with gestational age has not previously been investigated for the DECIDE model.…”
Section: Introductionmentioning
confidence: 99%